The Influence of Democratic Leadership Style and Work Discipline on Teacher Performance - Dinania, Dina (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2023)
The influence of democratic leadership style and work discipline on teacher performance at SMKN 1 Palangka Raya. This research aims to determine the influence of democratic leadership style and work discipline on the performance of SMKN 1 Palangka Raya teachers. This research method uses a quantitative approach, the number of samples in this research is 93 respondents. The sampling technique uses probability sampling. Data collection methods use interview, observation, questionnaire techniques, while the data analysis techniques used in this research use descriptive analysis techniques and multiple linear analysis techniques. The research results show that democratic leadership style and work discipline have a significant influence. influencing teacher performance at SMKN 1 Palangka Raya. And the results of the descriptive analysis stated that respondents agreed with the proposed indicators.